Queer Migration Politics : Activist Rhetoric and Coalitional Possibilities - Chávez, Karma R. (Book collections on Project MUSE., 2013)
Delineating an approach to activism at the intersection of queer rights, immigration rights, and social justice, this work examines a series of "coalitional moments" in which contemporary activists discover and respond to the predominant rhetoric, imagery, and ideologies that signal a sense of national identity.